Contrast‐Enhanced Ultrasound for Differentiation of Benign and Malignant Thyroid Lesions: Meta‐analysis. (24th October 2014) - Yu, Dongmei; Han, Yuna; Chen, Taotao
Abstract : Objective: Contrast‐enhanced ultrasound (CEUS) is a new noninvasive modality for the diagnosis of thyroid nodules. However, the performance of CEUS in differentiating malignant and benign thyroid nodules has not been systematically evaluated. This meta‐analysis was performed to assess the accuracy of CEUS in diagnosing thyroid nodules. Data Sources: PubMed, Embase, and the references of included studies were examined. Review Methods: We recorded the characteristics of the included studies and assessed the quality of each study using the Quality Assessment of Diagnostic Accuracy Studies tool. The pooled sensitivity, specificity, positive likelihood ratio (LR), negative LR, diagnostic odds ratio (DOR), and area under the curve (AUC) were calculated. We also evaluated the publication bias. Results: This meta‐analysis included 7 studies with a total of 597 thyroid nodules. The pooled the sensitivity, specificity, and positive and negative LR were 0.853, 0.876, 5.822, and 0.195, respectively. The DOR and AUC were 34.730 and 0.9162, respectively. Heterogeneity existed between the included studies. The results of subgroup analyses indicated that the evaluation processes are likely the predominant source of heterogeneity. No significant publication bias was observed. Conclusion: Contrast‐enhanced ultrasound is a promising noninvasive technique for the differential diagnosis of benign and malignant thyroid nodules and could be a valuable supplemental method to fine‐needle aspiration.